2016
DOI: 10.1007/s40273-016-0474-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Prophylaxis Treatment Strategies to Reduce the Incidence of Febrile Neutropenia in Patients with Early-Stage Breast Cancer or Non-Hodgkin Lymphoma

Abstract: ObjectiveThe objective of this study was to evaluate the cost effectiveness of no prophylaxis, primary prophylaxis (PP), or secondary prophylaxis (SP) with granulocyte colony-stimulating factors (G-CSFs), i.e., pegfilgrastim, lipegfilgrastim, filgrastim (6- and 11-day), or lenograstim (6- and 11-day), to reduce the incidence of febrile neutropenia (FN) in patients with stage II breast cancer receiving TC (docetaxel, cyclophosphamide) and in patients with non-Hodgkin lymphoma (NHL) receiving R-CHOP (rituximab, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…The results of our study aligned with Kulikov et al ( 2016 ) but disagree with those obtained by Fust et al ( 2015 , 2016 ), who found pegfilgrastim to be dominant when compared to lipegfilgrastim. This difference in conclusion may arise from the study design.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results of our study aligned with Kulikov et al ( 2016 ) but disagree with those obtained by Fust et al ( 2015 , 2016 ), who found pegfilgrastim to be dominant when compared to lipegfilgrastim. This difference in conclusion may arise from the study design.…”
Section: Discussionsupporting
confidence: 63%
“…There are very few studies assessing the cost-effectiveness of lipegfilgrastim compared to pegfilgrastim. Taking the Belgian payer perspective, Fust et al concluded that pegfilgrastim was cost-effective vs. lipegfilgrastim in patients with stage II breast cancer using Wang et al's risk estimate for FN of 1.39 (0.54–3.50) for lipegfilgrastim compared to pegfilgrastim (Fust et al, 2015 , 2016 ; Wang et al, 2015 ). Wang et al's risk estimate for FN was derived from a mixed treatment comparison (MTC) using a heterogeneous (i.e., non-breast cancer specific) cancer population and considering different studies designs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, from a Belgium perspective, Fust et al analyzed cost-effectiveness among patients with ESBC and NHL. The authors reported that secondary prevention dominated the no prophylaxis strategy, and primary prevention had highly favorable ICERs versus secondary prevention: e15,500 per QALY gained for breast cancer and e7800 for NHL 86 .…”
Section: Economics Of Csf Prophylaxismentioning
confidence: 99%
“…While the therapeutic value of PPG in EBC patients receiving docetaxel‐based regimens is well documented from several phase III trials; however, none were conducted on TCH‐treated patients. Economically, PPG has been considered both cost‐effective and cost‐reducing in patients with >20% high risk of FN, although some reports concluded no change in costs, because the reduction in hospitalization costs was offset by the cost of PPG administration . We strongly believe that in real life practice, the incidence of FN is patients receiving TCH is crossing the 20% boundary of cost‐effectiveness, and hence, we endorse Bayo et al.…”
mentioning
confidence: 70%